2015
DOI: 10.1007/s11418-015-0948-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of energy production by black ginger extract containing polymethoxy flavonoids in myocytes through improving glucose, lactic acid and lipid metabolism

Abstract: Enhancement of muscular energy production is thought to improve locomotive functions and prevent metabolic syndromes including diabetes and lipidemia. Black ginger (Kaempferia parviflora) has been cultivated for traditional medicine in Thailand. Recent studies have shown that black ginger extract (KPE) activated brown adipocytes and lipolysis in white adipose tissue, which may cure obesity-related dysfunction of lipid metabolism. However, the effect of KPE on glucose and lipid utilization in muscle cells has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…KPE was suggested to improve these decreases. We previously confirmed that PMFs, particularly 5,7-dimethoxyflavone in KPE, improved metabolism in muscle cells by activating AMPK [24]. AMPK is known to play a critical role in the regulation of energy homeostasis and is related to physical fitness, endurance, and fatigue [41][42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…KPE was suggested to improve these decreases. We previously confirmed that PMFs, particularly 5,7-dimethoxyflavone in KPE, improved metabolism in muscle cells by activating AMPK [24]. AMPK is known to play a critical role in the regulation of energy homeostasis and is related to physical fitness, endurance, and fatigue [41][42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 87%
“…anti-inflammatory, antioxidant [18][19][20][21], anticancer [22,23], muscular metabolismenhancing [24], anti-photoaging [25], phosphodiesterase (PDE)5 inhibitory [26], anti-cardiovascular disease [27], and viral protease inhibitory [28] activities). A large number of studies have investigated the bioactivities of black ginger extract (KPE), which is rich in PMFs [24,[29][30][31][32][33][34][35][36][37]. We also reported that PMFs in KPE improved muscular metabolism through AMP-activated protein kinase (AMPK) activation in myocytes [24].…”
Section: Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the existence of the whole organism to a certain extent depends on the functional activity of small intestine. Recently, for the correction of metabolic disorders in humans often use herbal remedies that are gentle action and mild side effects on the background of a broad therapeutic range [1][2][3][4][5][6]. The natural complex of biologically active substances -milk thistle -more than 2 thousand years uses to treat a range of diseases -from inflammation and arthritis to prostate carcinoma and breast cancer [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%